2015
DOI: 10.1177/1744629515592073
|View full text |Cite
|
Sign up to set email alerts
|

Family carers’ experience of the need for admission of their relative with an intellectual disability to an Assessment and Treatment Unit

Abstract: The admission of their relative was a time of increased vulnerability for carers in respect of maintaining a sense of self-identity. Engaging with services and professionals had a major influence on situating them within the social structure that makes up the formal system of support. This had a pivotal role in influencing and determining how participants identified with their sense of self.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Instead, perhaps the emotional consequences of a relative's admission presented here and by James (), yet not in studies around people with learning disabilities admitted to mainstream services, reflect public presuppositions of learning disability services. Future research could explore whether families' emotional reactions to admissions are different depending on hospital setting and, if so, what factors influence the difference.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Instead, perhaps the emotional consequences of a relative's admission presented here and by James (), yet not in studies around people with learning disabilities admitted to mainstream services, reflect public presuppositions of learning disability services. Future research could explore whether families' emotional reactions to admissions are different depending on hospital setting and, if so, what factors influence the difference.…”
Section: Discussionmentioning
confidence: 58%
“…In addition to appreciating regular, honest updates from staff, parents felt included in decisions around admission, discharge, medication and psychiatric diagnosis. In contrast, James () found that whilst family carers appreciated feeling listened to by ATU professionals, they did not always feel that their opinions were given weight. James' () recommended the balancing of expertise/power between services and families and this was evident in the current study and helped families to feel satisfied.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations